2019
DOI: 10.1002/cre2.205
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm formation on polyetheretherketone and titanium surfaces

Abstract: Objective Polyetheretherketone (PEEK) is a polymer used in devices in orthopedic and dental rehabilitation. The aim of this in vitro study was to compare biofilm formation by a range of important oral bacterial species on PEEK, blasted PEEK, commercially pure titanium (cp‐Ti), and titanium‐6 aluminium‐4 vanadium (Ti6Al4V). Material and methods Coin‐shaped samples were manufactured, and the surfaces were characterized using optical interferometry, scanning electron micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 40 publications
(62 reference statements)
2
27
0
Order By: Relevance
“…They concluded that no significant differences were found between smooth PEEK, machined commercially pure Ti, and Ti 6 Al 4 V and blasted PEEK was characterized by a higher biofilm formation. As highlighted by Barkarmo et al, the influence of superficial topography of the sample after 72 and 120 h is minimal and the significant differences that they found between smooth and blasted PEEK is more probably influenced by other factors, like the different chemical composition of the surfaces [30].…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…They concluded that no significant differences were found between smooth PEEK, machined commercially pure Ti, and Ti 6 Al 4 V and blasted PEEK was characterized by a higher biofilm formation. As highlighted by Barkarmo et al, the influence of superficial topography of the sample after 72 and 120 h is minimal and the significant differences that they found between smooth and blasted PEEK is more probably influenced by other factors, like the different chemical composition of the surfaces [30].…”
Section: Discussionmentioning
confidence: 88%
“…There are only few studies in literature that analyzed biofilm formation on PEEK surfaces. Barkarmo et al, have recently shown results about biofilm formation of different reference strains on PEEK and titanium surfaces at 72 and 120 h [30]. They concluded that no significant differences were found between smooth PEEK, machined commercially pure Ti, and Ti 6 Al 4 V and blasted PEEK was characterized by a higher biofilm formation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in antibacterial screens, collection strains are often used, whose virulence and adherence capability might differ from those found in wild-type strains isolated from implants [28,29]. In addition, the promotion of tissue integration is not often tested on antimicrobial screens, and, if it happens to be included, the testing is done separately from the antibacterial properties [30][31][32][33][34]. This is less than ideal as anti-biofilm/antibacterial capability and tissue integration should be preferably tested together.…”
Section: Introductionmentioning
confidence: 99%
“…Randomized controlled clinical trial showed that there is no statistically significant difference between the PEEK pillars compared to titanium and the PEEK did not cause bone resorption or inflammation, showing a promising alternative to titanium support [15]. Regarding the bacterial adhesion, the PEEK showed similar behavior when compared to cp-Ti, and Ti6Al4V [16].…”
Section: Editorialmentioning
confidence: 92%